Phylogenomics, taxonomy and conservation of the White’s skink (Scincidae: Liopholis whitii) species complex in south-eastern Australia - Parkin, Thomas; Swan, Gerry; Marshall, Lyndy; Bates, Keanu Garni; Mckellar, Ray Hunter-; Thompson, Nhalpa; Thompson, Warlpa; Parkin, Benjamin; Haines, Margaret L.; Farquhar, Jules E.; Lloyd, Ray; While, Geoffrey M.; et al. (Zootaxa, 2026)
White’s Skinks, Liopholis whitii (Lacépède 1804) are widely distributed throughout rocky habitats of temperate south-eastern Australia, with a highly disjunct population occurring in Mutawintji National Park in arid far western New South Wales. Based on an analysis of genome-wide nuclear single-nucleotide polymorphisms (SNPs) and an assessment of variation in morphology, we provide an appraisal of the group’s evolutionary history and re-evaluate the taxonomic status of candidate lineages. We reveal the presence of three major genetic lineages, including two lineages from temperate south-eastern Australia, and another representing the isolated arid population from Mutawintji National Park. We herein apply the name Liopholis whitii to the temperate “southern” lineage which occurs in South Australia, Victoria and Tasmania; resurrect the name Liopholis compressicauda (Quoy & Gaimard 1824) for the temperate “northern” lineage from southern Queensland, New South Wales, Australian Capital Territory and north-eastern Victoria; and describe the arid lineage from Mutawintji National Park as Liopholis mutawintji sp. nov. Liopholis mutawintji sp. nov. is of particular conservation concern and likely eligible for listing as Critically Endangered under multiple IUCN Red List Criteria.